Exclusive enteral nutrition in children and adolescents with Crohn disease: Dietitian perspectives and practice. (4th October 2020) - Burgess, Deirdre; Herbison, Kim; Fox, Julia; Collins, Tanya; Landorf, Emma; Howley, Peter
Abstract : Aim: In newly diagnosed paediatric Crohn disease, exclusive enteral nutrition (EEN) is recommended as a first‐line treatment for remission induction. However, EEN protocols vary internationally. The development of best practice protocols may make it easier to make definitive conclusions about optimal EEN therapy, and may improve patient outcomes. This study aims to determine the variations in current dietitian EEN practice within Australia and New Zealand (NZ) to inform a common EEN protocol in the future, and to gather perspectives on the need for nutrition resources for patients with inflammatory bowel disease (IBD). Methods: A questionnaire was created and emailed to paediatric dietitians working with gastroenterologists in public and private paediatric centres in Australia and NZ. Respondents were invited to provide details of their perspectives of EEN therapy and protocol details. Results: Eighteen paediatric dietitians responded to the questionnaire, 10 from Australia and 8 from NZ. There was clear consensus between respondents on the duration of EEN being 6 and 8 weeks, the need for close dietitian supervision while on EEN, and the method of food reintroduction. There was lack of consensus between dietitians regarding permitted concomitant foods whilst on EEN. This study also determined a potential benchmarking relationship between IBD dietitian hours and numbers of patients on EEN per year in a centre. Conclusions: Paediatric dietitians in Australia and NZ are mostly aligned in their practice of EEN. Development of a standard EEN protocol, and patient IBD resources, will further align practice and allow for greater research possibilities.